The cross‐sectional association of cognitive stimulation factors and cognitive function among Latino adults in Hispanic Community Health Study/Study of Latinos (HCHS/SOL) - Priscilla M. Vásquez; Wassim Tarraf; Adit Doza; Maria J. Marquine; Krista M. Perreira; Neil Schneiderman; Donglin Zeng; Jianwen Cai; Carmen R. Isasi; Martha L. Daviglus; Hector M. González (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract Introduction Higher cognitive stimulation (CS) is associated with improved cognition. Sources of CS among Hispanics/Latinos are understudied. Methods In the Hispanic Community Health Study/Study of Latinos 2008 to 2011 (n = 9438), we used finite mixture models to generate latent CS profiles, and multivariate linear regressions to examine associations with cognition in Hispanic/Latino adults (45–74 years). CS included education, occupation, social network, and acculturation. Cognitive measures included the Six‐Item Screener, Brief‐Spanish English Verbal Learning Test Sum and Recall, Controlled Oral Word Association Test, Digit Symbol Substitution, and Global Cognition. Results Two CS profiles emerged, and were labeled “typical” and “enhanced.” The enhanced CS profile (22%) had more family connections, bicultural engagements, skilled/professional occupations, education, and higher cognitive scores. Discussion An enhanced CS profile emerged from contextual and culturally relevant factors, and was associated with higher cognitive scores across all measures. This provides initial evidence on how factors coalesce to shape cognitive protection in Hispanics/Latinos.